Uranium and cadmium provoke different oxidative stress responses in Lemna minor L. (29th July 2014) - Horemans, N.; Van Hees, M.; Van Hoeck, A.; Saenen, E.; De Meutter, T.; Nauts, R.; Blust, R.; Vandenhove, H.
Abstract: Common duckweed ( Lemna minor L.) is ideally suited to test the impact of metals on freshwater vascular plants. Literature on cadmium (Cd) and uranium (U) oxidative responses in L. minor are sparse or, for U, non‐existent. It was hypothesised that both metals impose concentration‐dependent oxidative stress and growth retardation on L. minor . Using a standardised 7‐day growth inhibition test, the adverse impact of these metals on L. minor growth was confirmed, with EC50 values for Cd and U of 24.1 ± 2.8 and 29.5 ± 1.9 μm, respectively, and EC10 values of 1.5 ± 0.2 and 6.5 ± 0.9 μm, respectively. The metal‐induced oxidative stress response was compared through assessing the activity of different antioxidative enzymes [catalase, glutathione reductase, superoxide dismutase (SOD), ascorbate peroxidase (APOD), guaiacol peroxidase (GPOD) and syringaldizyne peroxidase (SPOD)]. Significant changes in almost all antioxidative enzymes indicated their importance in counteracting the U‐ and Cd‐imposed oxidative burden. However, some striking differences were also observed. For activity of APODs and SODs, a biphasic but opposite response at low Cd compared to U concentrations was found. In addition, Cd (0.5–20 μm ) strongly enhanced plant GPOD activity, whereas U inhibited it. Finally, in contrast to Cd, U up to 10 μm increased the level of chlorophyll a and b and carotenoids. In conclusion, although U and Cd induce similar growth arrest in L. minor, the U‐induced oxidative stress responses, studied here for the first time, differ greatly from those of Cd.